Do Chief Sustainability Officers matter to sustainability reporting? : Evidence from green pioneer France - Lau, NgaSing; Tyll, Ladislav; Bruder Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
In response to increasing institutional pressure for transparent sustainability reporting, this research investigates the contribution of Chief Sustainability Officers (CSOs) within French listed corporations. Moving beyond simple presence, the study evaluates how their sustainability competence shapes reporting disclosure, external verification practices, and the use of standardized frameworks such as GRI. Drawing on stakeholder, legitimacy, and upper- echelons perspectives, the analysis applies a panel regression model to 950 firm-year observations from 2017 to 2024. The findings reveal limited influence from mere CSO designation but suggest modest improvements in disclosure when CSOs demonstrate relevant expertise or when reporting oversight is formally anchored at the CEO level. These insights highlight the symbolic vs. substantive debate surrounding CSO appointments and offer implications for firms aiming to enhance their ESG credibility in compliance-focused environments.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses